The impact of climate change and biodiversity loss on the health of children: An ethical perspective - Phoebe C. M. Williams; Phoebe C. M. Williams; Phoebe C. M. Williams; Phoebe C. M. Williams; Justin Beardsley; Justin Beardsley; David Isaacs; David Isaacs; Anne Preisz; Anne Preisz; Ben J. Marais; Ben J. Marais; et al. (Frontiers Media S.A., 2023)
The reality of human induced climate change is no longer in doubt, but the concerted global action required to address this existential crisis remains inexcusably inert. Together with climate change, biodiversity collapse is increasingly driving the emergence and spread of infectious diseases, the consequences of which are inequitable globally. Climate change is regressive in its nature, with those least responsible for destroying planetary health at greatest risk of suffering the direct and indirect health consequences. Over half a billion of the world's children live in areas vulnerable to extreme weather events. Without immediate action, the health of today's children and future generations will be compromised. We consider the impact of biodiversity collapse on the spread of infectious diseases and outline a duty of care along a continuum of three dimensions of medical ethics. From a medical perspective, the first dimension requires doctors to serve the best interests of their individual patients. The second dimension considers the public health dimension with a focus on disease control and cost-effectiveness. The neglected third dimension considers our mutual obligation to the future health and wellbeing of children and generations to come. Given the adverse impact of our ecological footprint on current and future human health, we have a collective moral obligation to act.